A avaliação como dispositivo de subjetivação - Bertoldo, Fernanda (My University, 2014)
This master‘s thesis is anchored on the research line for History and Philosophy of Education at the Master‘s Program at the University of Caxias do Sul and it discusses the processes of school assessment under a genealogical perspective. The research problem questions the ways through which school assessment has been functioning as a device in the production of modes of subjectivation. As theoretical references, the concepts for devices and subjectivation developed by Michel Foucault are the main support. The investigation is confined to documents that legislate on processes of education and, more specifically, that rule the process for school assessment. The first document used in the analysis is dated January 1828; from it the statements regarding the process of assessment up to the latest LDB (Lei n. 9.394/96) and the stated opinions and decrees resulting from it. The documents were obtained – in its majority – at a document collection called Base Legis. In the documents, conditions for the possibilities of a discourse on assessment in each discourse formation are investigated. It is pointed out that the analyses do not operate based on judgements regarding assessment processes, but on the historical conditions of its functioning. Hence, the assumption that assessment turns out to be a certain device woven in different relationships of power and knowledge, in the production of certain ways of subjectivation. The analysis starts from the notion of historical discontinuity. There is an attempt to highlight the dislocations in discourses that produce ruptures in the functioning, here limited to the production – via assessment – of ―good Christians‖ and ―good citizens‖, from a model of exclusion and one of inclusion, as well as the production of disciplinary logic in assessment going through the subjects of school. The analysis is not forged in such a way as to characterize a global history, not even a linear history, but from the notion of discontinuity of history. What has been attempted was to produce a problematization about the constitution of that subject of the education by the assessment process, and that was only possible with the rupture of the notion of an identity subject, which is unitary and autonomous. There is an interest on the constitution of the ways of being, in their relationships with power and knowledge. Thus, assessment is understood as a device that encompasses and sets up the subjects as a network that is woven in the architecture of schools and out of it; going through behaviors agreed upon, the dynamic of circulation; it is present in the valuation of moral values, in scientific utterances, in legislations, in timeline organizations; in short, in the entanglement of what one is, of what one says, and what one does. That way, it is possible to state that the device is inscribed in a line of power, connected to configurations of power that can put into effect certain ways of subjectivation, which in this process produce citizens, the included, disciplined and standardized ones who cover the entire social body.
A presente dissertação ancora-se na Linha de Pesquisa História e Filosofia da Educação do Mestrado em Educação da Universidade de Caxias do Sul e problematiza os processos de avaliação escolar em uma perspectiva genealógica. O problema de pesquisa questiona as formas pelas quais a avaliação escolar vem funcionando como um dispositivo na produção de modos de subjetivação. Como referencial teórico, são tomados, principalmente, os conceitos de dispositivo e subjetivação desenvolvidos por Michel Foucault. A investigação está circunscrita a documentos que legislam sobre os processos de educação e, mais especificamente, que regulam o processo de avaliação escolar. O primeiro documento utilizado na análise é datado de janeiro de 1828; a partir dele, apuram-se os enunciados sobre o processo de avaliação até a última LDB (Lei n. 9.394/96) e os pareceres e decretos decorrentes. Os documentos foram obtidos, na maior parte, em um acervo de leis e documentos denominado Base Legis. Nos documentos, buscam-se as condições de possibilidades de um discurso de avaliação em cada formação discursiva. Salienta-se que as análises não operam com juízos a respeito dos processos de avaliação, mas com as condições históricas de seu funcionamento. Diante disso, considera-se o pressuposto de que avaliação vem a ser um determinado dispositivo tecido em diferentes relações de poder e saber, na produção de determinados modos de subjetivação. A análise é produzida a partir da noção de descontinuidade da história. Procura-se pôr em evidência os deslocamentos de discursos que produzem rupturas nos modos de funcionamento, aqui circunscritos na produção – via dispositivo da avaliação – de ―bons cristãos‖ e ―bons cidadãos‖, de um modelo de exclusão e outro de inclusão, bem como a produção da lógica disciplinar na avaliação, atravessada nos sujeitos da escola. A análise não é forjada de modo a caracterizar uma história global, nem mesmo uma forma linear de história, mas a partir da noção de descontinuidade da história. O que se tentou produzir foi uma problematização acerca da constituição desse sujeito da educação pelo processo de avaliação, e isso só foi possível com o rompimento da noção de um sujeito identitário, unitário e autônomo. Interessa a constituição dos modos de ser, em suas relações de poder e saber. Entende-se, assim, a avaliação com um dispositivo – que engloba e coloca em funcionamento os sujeitos, como uma rede que se tece nas arquiteturas das escolas e fora delas; passa pelos comportamentos convencionados, pela dinâmica de circulação; está presente na valoração dos valores morais, nos enunciados científicos, nas legislações, nas organizações espaçotemporais, enfim, nos meandros do que se é, do que se faz e do que se fala. Dessa forma, pode-se afirmar que o dispositivo está inscrito numa linha de força, ligado a configurações de poder que efetivam determinados modos de subjetivação, os quais, nesse processo, produzem os cidadãos, os incluídos e os disciplinados e normatizados que cobrem todo corpo social.
Keywords: Avaliação educacional; Educação; Genealogia; Assessment; Device; Subjectivation